2006
DOI: 10.1007/s11916-006-0024-0
|View full text |Cite
|
Sign up to set email alerts
|

Head trauma and cluster headache

Abstract: Post-traumatic cluster headache (CH) is a very rare occurrence. Only one such case has been verified in the literature thus far. On the other hand, a non-casual association is almost certain to exist between previous head trauma and future CH onset. Considering the generally long interval of time separating the two events, it is not easy to accurately explain the nature of the head trauma/CH relationship. Head trauma may damage extra- or intracranial peripheral or central nervous structures, hence predisposing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…However, migraine type was most prevalent, but, interestingly, TAC type was the second most prevalent, raising the possibility that more focal, severe and episodic headaches may suggest a relationship with the mechanism of injury. In an historical footnote, those papers relating cluster headache patients to head injury or violence suggest that the pugnacious nature of males with cluster headaches, including the authors' noting of alcohol seeking, may be a part of the reason for some of this association (64)(65)(66)(67). The relevance of this to service members is not implied, but war, by definition, involves fighting.…”
Section: Finkel Et Almentioning
confidence: 99%
“…However, migraine type was most prevalent, but, interestingly, TAC type was the second most prevalent, raising the possibility that more focal, severe and episodic headaches may suggest a relationship with the mechanism of injury. In an historical footnote, those papers relating cluster headache patients to head injury or violence suggest that the pugnacious nature of males with cluster headaches, including the authors' noting of alcohol seeking, may be a part of the reason for some of this association (64)(65)(66)(67). The relevance of this to service members is not implied, but war, by definition, involves fighting.…”
Section: Finkel Et Almentioning
confidence: 99%
“…5,6 An important review published in 2006 by Manzoni et al, clearly demonstrated the significant relation between head trauma and cluster headache. 7 The temporal relationship between headache onset and head injury can be variable, ranging from immediate onset to 30 years after the trauma. 5 Turkewitz et al, reported one case of post-traumatic cluster headache, with clinical symptoms emerging 6 days after the trauma, so with close proximity between head injury and the onset of cluster headache.…”
Section: Discussionmentioning
confidence: 99%
“…50,51 Frequently, headaches phenotypically resembling chronic tension-type headache coexist with episodic migraine or migrainous headache. 48 Very rare case reports have attributed trauma to the onset of headaches phenotypically similar to several of the less common primary headache disorders, including cluster headache, [52][53][54][55] hemicrania continua, 56 SUNCT, 57 and chronic paroxysmal hemicrania. 58…”
Section: Pth In Unique Populations-the Military and Sports-mentioning
confidence: 99%